Down Regulation of CD4 Expression following Isolation and Culture of Human Monocytes - Graziani-Bowering, Gina M. (American Society for Microbiology, 2000)
The down regulation of CD4 by cultured monocytes has been observed by our group and by other investigators. Flow cytometric experiments were done to examine which factors might influence this phenomenon. The addition of lipopolysaccharide, granulocyte-macrophage colony-stimulating factor, macrophage colony-stimulating factor, or interleukin-10 to monocyte cultures failed to inhibit the decrease in monocyte CD4 expression routinely observed following overnight culture. The down regulation was an adherence-independent phenomenon and was not influenced by the type of anticoagulant into which the peripheral blood was collected or by the presence or absence of lymphocytes within the cultures. The avoidance of the use of Ficoll-Paque to isolate peripheral blood mononuclear cells did not prevent monocyte CD4 down regulation. Finally, by tagging monocyte CD4 with an anti-CD4 phycoerythrin-conjugated monoclonal antibody prior to culture, we were able to determine that the down regulation observed was the result of the internalization of the molecule. At this time, we conclude that the observed down regulation of monocyte CD4 is probably due to the differentiation of blood monocytes into tissue culture-derived macrophages rather than to some artifact of the isolation procedure.